Peppermint essential oil enhances the vase life of Dendrobium orchids - Montinee Teerarak; Komkhae Pilasombut; Chamroon Laosinwattana (Heliyon, 2024)
orchids.
Keywords: Essential Oils and Antimicrobial Activity; Flowering Plant Growth and Cultivation; Plant Pathogens and Fungal Diseases